The impact of professional networking and burnout on the organizational and professional commitment of human resources professionals - Barber, Eric; Werner, Jon M. (International Journal of Human Resource Development Practice Policy & Research, 2024)
Research on burnout has not focused much attention on human resource (HR) professionals, who are often the link between managers and employees. HR professionals have become more integral in organizations’ strategies, processes and protocols. Burnout and lack of both professional and organizational commitment from this group of employees could be detrimental to organizations. This study examines the effects of professional networking and burnout on the organizational and professional commitment of HR professionals, as well as the potential moderating relationship of professional networking on the relationships between job burnout and organizational and professional commitment through professional networking channels such as LinkedIn forums, professional memberships in organizations like the Society for Human Resource Management (SHRM), or other HR support work groups. A positivist approach using Ordinary Least Squares (OLS) was utilized to examine these relationships, and burnout was significantly and negatively related to both professional and organizational commitment. Further, professional networking had a significant positive influence on the relationship between burnout and commitment, meaning that burnout had a less negative impact on commitment when networking was higher. The results provide insight into factors that assist HR professionals in lessening the effects of burnout, while also increasing organizational and professional commitment.